Legal features of the mortgage as a form of collateral under the laws of the Republic of Kazakhstan. (Journal of actual problems of jurisprudence, 2016)
This article is devoted to features of a mortgage as type of pledge. Regulation of questions of a turn of real estate in the conditions of market economy, received big value. One of the developing directions of the market of real estate is the real estate mortgage. Mortgage, being the financial mechanism of creation and attraction of additional financial means, it is capable to solve an absence problem at these or those participants of a civil turn of enough of these means. Therefore today mortgage lending is one of the most actual directions of crediting.
Keywords: mortgage; real estate; objects of civil law; the legal regime of real estate